2015
DOI: 10.1039/c5cc02113h
|View full text |Cite
|
Sign up to set email alerts
|

Metal–organic framework biosensor with high stability and selectivity in a bio-mimic environment

Abstract: A water-stable copper metal-organic framework (MOF), {[Cu2(HL)2(μ2-OH)2(H2O)5]·H2O}n (1, H2L = 2,5-dicarboxylic acid-3,4-ethylene dioxythiophene), was applied for the electrochemical detection of ascorbic acid (AA) without further post-modification. A glass carbon electrode covered with 1 was used as a biosensor for the simultaneous detection of AA and L-tryptophan (L-Trp) from both a single-component solution and a bio-mimic environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(25 citation statements)
references
References 28 publications
0
25
0
Order By: Relevance
“…MOFs show potential as electrochemical sensing surface modifiers because of their high surface area and pore volume, good absorbability, and high catalytic activity [ 69 , 70 ]. With the rapid development of synthesis methods, stable MOFs with high electrical conductivity have been successfully designed and synthesized [ 71 73 ]. However, most MOFs still have poor electrical conductivity and relatively low stability in aqueous solution; this is a result of the reversible nature of the coordination bonds.…”
Section: Mof-based Sensors In Aqueous Solutionmentioning
confidence: 99%
“…MOFs show potential as electrochemical sensing surface modifiers because of their high surface area and pore volume, good absorbability, and high catalytic activity [ 69 , 70 ]. With the rapid development of synthesis methods, stable MOFs with high electrical conductivity have been successfully designed and synthesized [ 71 73 ]. However, most MOFs still have poor electrical conductivity and relatively low stability in aqueous solution; this is a result of the reversible nature of the coordination bonds.…”
Section: Mof-based Sensors In Aqueous Solutionmentioning
confidence: 99%
“…The most commonly seen example is the amperometric glucose sensor [1], which has been widely available on the market. During the past five years, numerous zinc-based and copper-based MOFs have been utilized in electrochemical sensing systems operated in phosphate buffer solutions or alkaline electrolytes to detect a range of species including hydrogen peroxide [126][127][128][129], glucose [130], L-cysteine [131], L-tryptophan [132], ascorbic acid [132,133], dopamine [134], and nitrite [135,136]. In 2015, K. C. Ho et al demonstrated the use of a Zr-MOF, MOF-525, to electrochemically detect nitrite in aqueous electrolytes with a natural pH (see Figure 8a) [43].…”
Section: Electroanalysismentioning
confidence: 99%
“…MOFs are notable for their large surface area, highly porous structures, and tunable catalysis capability, all of which are highly demanded for biological sensing. When proper organic ligands are chosen, MOFs can be conductive or semiconductive, leading to development of several electronic devices such as field effect transistors, electric double‐layer capacitors, and sensors . Despite various demonstrations of MOFs in chemical sensing, they have never been demonstrated in implantable biological sensing and integrated with flexible sensors to conduct multichannel determination of nutriments.…”
mentioning
confidence: 99%